Analisis Pengembangan Pemilihan Media Bahan Ajar - Yespa Warinta; Kinanti Oktria; Jihan Annisa Zarah; Ariyanto. R; Rahmayuni Rahmayuni; Wismanto Wismanto (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
In the development of media selection, teaching materials are part of a learning development that cannot be separated from other learning components in a system. Therefore, the selection of media has a variety and methods in accordance with various development models for selecting media for existing teaching materials, including the criteria used in selecting the media. This research aims to determine developments in the selection of teaching material media that will be used in the learning process and as a reference for teachers to develop a teaching material media in the learning process. This research uses qualitative research methods with the type of library research. Qualitative research is the process of producing information in the form of notes and descriptive data. The results of this research show that the development in selecting teaching material media is: (1). selecting teaching materials that fulfill one of the interesting teaching materials and helps students achieve competency and aims to help in the students' learning process, (2) determining the choice of teaching material criteria. must have the ability to improve students' memory, (3) teachers must be skilled in using teaching materials that will be used in learning.